THE EFFECT OF ORGANIZATIONAL JUSTICE ON EMPLOYEE PERFORMANCE JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT DURENMANDIRI FORTUNA JAMBI - Faizah, Naela Mikyalul (PT. Anagata Sembagi Education, 2024)
The study aims to determine the effect of organizational justice on employee performance on job satisfaction as an intervening variable. The target of this research is the employees of PT Duren Mandiri Fortuna Jambi. The population and sample for this study were employees of PT. Duren Mandiri Fortuna Jambi, totaling 300 employees with a sample size of 75 employees. This research is quantitative research, the data used in this study were obtained through a questionnaire method. The data analysis method of this research is descriptive statistical analysis using Structural Equation (SEM) techniques, with Partia lLeastSquare (PLS) as a processing tool using the SmartPLS program (v.3.2.9). The results of this study prove that organizational justice has a positive and significant effect on employee performance, organizational justice has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance, organizational justice has a positive and significant effect on employee performance, job satisfaction as an intervening variable at PT. Duren MandiriFortuna Jambi. So it can be concluded from the research results that HR policies to improve cooperation among coworkers, communication between leaders and subordinates must be well established to provide understanding to employees and job satisfaction in providing promotion opportunities are recommended to be given fairly and in accordance with the requirements for all employees.